IMPLEMENTASI PROGRAM PEMBINAAN KEPRIBADIAN MELALUI KEGIATAN TERAPI MINDFULNESS ANAK BINAAN DI LPKA KELAS I MEDAN - Edwin Afdhallah; Ade Cici Rohayati (Ensiklopedia of Journal, 2025)
This study aims to describe and analyze the implementation of a personality development program through mindfulness therapy activities for juvenile inmates at the Special Development Institution for Children (LPKA) Class I Medan. The focus of the research includes how the program is implemented, as well as the supporting and inhibiting factors during its execution. This research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The implementation framework refers to David C. Korten’s theory. Additionally, the study utilizes the concept of mindfulness. The findings show that the mindfulness therapy program has been implemented in a structured manner and addresses the psychological needs of the juvenile inmates. The program materials are adapted to the participants’ conditions and delivered by facilitators who are capable of building meaningful emotional connections. The activities encourage participants to become more focused, calm, and aware of their emotions and life experiences. Juvenile inmates demonstrated active participation, openness, and gradual changes in behavior. Key supporting factors include institutional support, facilitator commitment, and a humane approach to activities. Meanwhile, the main challenges are limited facilities, a restricted number of participants per session, and uneven understanding of mindfulness among all participants. Nevertheless, the program has made a positive contribution to the character development of the juvenile inmates and presents a promising alternative approach to psychological rehabilitation within correctional settings.Keywords: mindfulness; personality development; juvenile inmates; LPKA; program implementation.